Toward a Uniform Court Practice in the Republic of Macedonia - Jelena Ristik (European Scientific Journal, ESJ, 2017)
Despite the different perceptions regarding the status and treatment of the court practice in the Republic of Macedonia, judicial and state authorities are united in their view that there is a need for achieving a higher degree of uniformity of court practice. The need for a higher degree of uniformity of court practice was also noted by the European Union within its latest reports on the progress of the Republic of Macedonia as a candidate country for membership in the European Union as well as in the recent Report on Macedonia: Assessment and recommendations of the Senior Experts' Group on systemic Rule of Law issues 2017. This paper will try to resolve the various different interpretations as regards the court practice in Macedonia and define its role, treatment and application. This will be achieved mainly through analysis of the relevant national legislation. Further, possible new tools will be considered for achieving a greater uniformity of court practice. It will be argued that the court practice should serve as an additional means of argumentation within the reasoning of court judgments, which will contribute to increasing the degree of uniformity of court practice and rule of law as well. Finally, some suggestions will be given in order to provide for better conditions for the Supreme Court to exercise its constitutional competence to ensure the uniform application of the laws by the courts and thus ensure the existence of a uniform court practice.